THE SPECIFIC ORDINATION AND CLUSTERING OF MANGROVE ECOSYSTEM IN SEGARA ANAKAN - Hilmi, Endang; Junaidi, Teuku; Mahdiana, Arif; Prayogo, Norman Arie; Dewi, Rose; Rahayu, Sri (Indonesian Journal of Forestry Research, 2024)
Mangrove ecosystem has specific ordination and clustering  following the adaptation toward the environment properties and species competition.  This research aimed to develop a specific ordination to support ecosystem stability. The research was carried out with a multidimensional system using density and environmental properties with similarity and Euclidian distance indexes. The results showed that West Segara Anakan had 6 ordination areas, and East Segara Anakan had 5 ordinations with the range density of 68-3373 trees/ha and 550-2975 trees/ha. Based on environmental properties, WSAL had nitrate, phosphate, pyrite, water and soil pH, and water salinity levels of 10.57-31.44 mg/lt, 8.44-22.89 mg/lt, 1.03-1.57 %, 5.60-7.78, 6.58-7.03, and 24.15-33.85 ppt, respectively. In ESAL, nitrate, phosphate, pyrite, water and soil pH, and water salinity were within the range of 19.72-28.98 mg/lt, 10.83-19.72 mg/lt, 1.28-2.91%, 6.35-7.05, 5.91-6.23, and 18.00-32.33 ppt. Furthermore, specific ordination showed that Avicennia marina, Rhizophora stylosa, Rhizophora apiculata, and Nypa frutican had the highest level of adaptation. I special thanks for research Terapan Unsoed 2023 to support this research.